Integração e subversão: a educação da Frente Negra Brasileira em princípios do século XX em São Paulo - Rufino, Anderson de Oliveira (2025)
By reading the issues of the periodical A Voz da Raça, the official communication vehicle of the Frente Negra Brasileira (Brazilian Black Front), we sought to highlight some of the meanings and the role attributed to education by the largest Black association, which emerged in the early 20th century in São Paulo. This educational aspect, then, favored the unification of certain segments of the Black population during that period around collective goals, both identity-based and in the fight against racism, and also with a view to more equal integration into society. Therefore, we took a historical look back, establishing some of the main social, political, economic, and racial characteristics that shaped the context of the period in question, particularly regarding the advance of modernity and its racial and socioeconomic contradictions in Brazil, and more specifically, in the city of São Paulo. We thus sought to demonstrate how socioeconomic and racial aspects influence each other and are essential to understanding Brazilian social reality.